Seagrass structural and elemental indicators reveal high nutrient availability within a tropical lagoon in Panama - Gaubert-Boussarie, Julie; Altieri, Andrew H.; Duffy, J. Emmett; Campbell, Justin E. (PeerJ (San Francisco, CA), 2021)
Seagrass meadows are valued coastal habitats that provide ecological and economic benefits around the world. Despite their importance, many meadows are in decline, driven by a variety of anthropogenic impacts. While these declines have been well documented in some regions, other locations (particularly within the tropics) lack long-term monitoring programs needed to resolve seagrass trends over time. Effective and spatially-expansive monitoring within under-represented regions is critical to provide an accurate perspective on seagrass status and trends. We present a comprehensive dataset on seagrass coverage and composition across 24 sites in Bahía Almirante, a lagoon along the Caribbean coast of Panama. Using a single survey, we focus on capturing spatial variation in seagrass physical and elemental characteristics and provide data on key seagrass bio-indicators, such as leaf morphology (length and width), elemental content (% nitrogen and phosphorus) and stable isotopic signatures ( δ 13 C and δ 15 N). We further explore relationships between these variables and water depth (proxy for light availability) and proximity to shore (proxy for terrestrial inputs). The seagrass assemblage was mostly monospecific (dominated by Thalassia testudinum) and restricted to shallow water (<3 m). Above-ground biomass varied widely, averaging 71.7 g dry mass m −2 , yet ranging from 24.8 to 139.6 g dry mass m −2 . Leaf nitrogen content averaged 2.2%, ranging from 1.76 to 2.57%, while phosphorus content averaged 0.19% and ranged from 0.15 to 0.23%. These values were high compared to other published reports for T. testudinum, indicating elevated nutrient availability within the lagoon. Seagrass stable isotopic characteristics varied slightly and were comparable with other published values. Leaf carbon signatures ( δ 13 C) ranged from −11.74 to −6.70‰ and were positively correlated to shoreline proximity, suggesting a contribution of terrestrial carbon to seagrass biomass. Leaf nitrogen signatures ( δ 15 N) ranged from −1.75 to 3.15‰ and showed no correlation with shoreline proximity, suggesting that N sources within the bay were not dominated by localized point-source discharge of treated sewage. Correlations between other seagrass bio-indicators and environmental metrics were mixed: seagrass cover declined with depth, while biomass was negatively correlated with N, indicating that light and nutrient availability may jointly regulate seagrass cover and biomass. Our work documents the response of seagrass in Bahía Almirante to light and nutrient availability and highlights the eutrophic status of this bay. Using the broad spatial coverage of our survey as a baseline, we suggest the future implementation of a continuous and spatially expansive seagrass monitoring program within this region to assess the health of these important systems subject to global and local stressors.